Defining an Evaluation Protocol for the Infant with Fetal Echogenic Bowel - Alsup, Kendall; Pearson, Jessica L.; Bowe, Andrew; Woodham, Padmashree C. (American Journal of Perinatology, 2024)
Objective This study aimed to develop an algorithm for pediatricians to use for infants diagnosed with fetal echogenic bowel (FEB) to ensure that each patient is fully evaluated for possible complications while avoiding unnecessary morbidity and mortality and health care-associated costs.Study Design This was a prospective cohort of neonates for which a diagnosis of FEB was made during a Level 2 anatomy ultrasound between February 2016 and January 2017. Women diagnosed with FEB were offered perinatal genetic counseling and testing. These women also received increased third trimester fetal surveillance, including daily fetal kick counts, fetal growth scans every 3 to 4 weeks beginning at 28 weeks, and weekly fetal nonstress test (NST) and/or BPP beginning at 32 weeks. After delivery, neonates received a postnatal evaluation including birth weight, gestational age at birth, presence of other abnormalities, and associated perinatal morbidity and mortality. Comparison between findings was performed using chi-square test. All statistical evaluation was performed using SPSS.Results Among 919 pregnant patients who received Level 2 anatomy ultrasounds at a Regional Perinatal Center during the study period, 70 received a diagnosis of FEB. Of those diagnosed with FEB, 52 (74.3%) delivered at the same Regional Medical Center. Of these 52 delivered infants, 3 (5.8%) were intrauterine fetal demises (IUFDs) and 4 (7.6%) had unaffected twins. Only one multifetal gestation had the diagnosis of FEB in both the twins. Only 19 of the infants delivered had a kidney, ureter, and bladder X-ray (KUB) performed secondary to prematurity or abnormal exams.Conclusion This study showed that the majority of infants diagnosed with FEB had a normal exam following delivery, and that most of the neonatal outcomes of neonatal intensive care unit admissions and other neonatal complications are a result of prematurity rather than FEB. Although the algorithm did not have significant results, it is easy to follow and implement in larger studies.Key Points
Keywords: fetal echogenic bowel; ultrasound; neonate; pregnancy